Evolution of physical power sports during the Middle Ages - Ahmed Hassan, Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
Given the periods that this volume intends to cover, there seems to be little room for Quebec. Indeed, sport only became socially and economically important in our country in the twentieth century. However, since men have lived there for millennia, sports exercises have been practiced for a very long time. Indeed, our country has the advantage of having an authentic heritage both from the point of view of sports and physical education. In its report, the Commission on Canadian Studies writes, "Canadians seem to suffer from cultural amnesia when it comes to considering this important aspect of our history and our national life..." 1. Quebeckers would be uncomfortable doing like too many Canadians by giving no place to studies in the history of sport. Moreover, we will treat a lot of Quebec, whose sporting history is little known to historians. When we talk about physical activity in New France, we will overflow the current province of Quebec, as New France extended to New Orleans. There will be much question of the Indians and a little of the French until the eighteenth century.